Peran Kompetensi Manajerial Gembala dalam Mewujudkan Visi “Terwujudnya Jemaat yang Misioner” di Gereja KIBAID Jemaat Marinding - Yunita Sombolayuk; Firdaus Firdaus; Setblon Tembang (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
This research is motivated by the fact that church growth cannot be separated from understanding the importance of the management of a congregational pastor in realizing the church's vision. In this case, the role of the pastor's managerial competence is really needed to achieve the church's vision. KIBAID Church is an evangelical church with the vision of "Creating a missionary congregation." Implementation of the vision of "Creating a Missionary Congregation" is very dependent on local churches, one of which is the KIBAID church of the Marinding Congregation. This research aims to discover the role of the pastor's managerial competence in the vision of "Creating a Missionary Congregation" at the KIBAID Congregation of Marinding Church. This research is descriptive qualitative research. The findings in this research are that the pastor's role is to complete the vision with planning, the pastor's role is to share the vision, the pastor's role is to raise enthusiasm, the pastor's role is as a driving force in the church, the pastor's role is as a trainer for the next leader. Penelitian ini dilatarbelakangi oleh fakta bahwa pertumbuhan gereja tidak terlepas dari pemahaman akan pentingnya manajemen seorang gembala jemaat dalam mewujudkan visi gereja. Dalam hal ini peran kompetensi manajerial gembala sangat dibutuhkan untuk mencapai visi gereja. Gereja KIBAID merupakan salah satu gereja injili dengan visi “Terwujudnya Jemaat yang Misioner”. Implementasi visi “Terwujudnya Jemaat yang Misioner” sangat bergantung pada gereja lokal, salah satunya adalah gereja KIBAID Jemaat Marinding. Penelitian ini bertujuan untuk menemukan peran kompetensi manajerial gembala dalam visi “Terwujudnya Jemaat yang Misioner” di Gereja KIBAID Jemaat Marinding. Penelitian ini merupakan penelitian kualitatif deskriptif. Adapun hasil temuan dalam penelitian ini yaitu gembala berperan untuk melengkapi visi dengan perencanaan, gembala berperan membagikan visi, gembala beperan untuk membangkitkan semangat, gembala berperan sebagai penggerak dalam gereja, gembala sebagai pelatih bagi pemimpin berikutnya.